Poesía popular ecuatoriana - Padilla Dacto, Ely Magaly (2016)
The contribution of folk poetry on the school stage has a key role for student learning by making them more independent intellectually, improving linguistic articulation and strengthening the emotional bond, which is necessary for the overall development of students. To make this project has taken as reference the realization of a diagnosis through observation of students of the Education Unit Narciso Cerda Maldonado, it has been the lack of interest in poetry which is reflected in learning this literary genre, for this reason underlying the need for this research work, it is necessary to rethink the integral formation of the students from deepen cultural values reaching expression in popular poetry, aspirational remedy a related problem. It is necessary to stimulate interest, creation, promotion, dissemination of Ecuadorian folk poetry using materials from the environment, through educational workshops, poetry contests in the festivities of the unit, in order to strengthen our cultural identity. We use the method of modeling because it is fundamental research process, we help with the design methodologies and strategies needed for the process of working with folk poetry and the formation of cultural values. It is expected to result in students determine the current state of creation, dissemination of Ecuadorian folk poetry and the formation of cultural values. rethinking the role of popular poetry in education, finding alternatives to guide a process of change from poetry is necessary. The participation of teachers in education should be the strength for the study and spread of Ecuadorian folk poetry adapting it to curriculum planning that allows us to motivate different areas as a teaching resource to promote this art and as a consequence we to be critical, reflective, authors, poets local and national students.